Impact of the Novel Coronavirus 2019 (COVID-19) Pandemic on Head and Neck Cancer Care - Thompson, Joshua Adam; Lubek, Joshua E.; Amin, Neha; Joy, Reju; Dyalram, Donita; Ord, Robert A.; Taylor, Rodney J.; Wolf, Jeffrey S.; Mehra, Ranee; Cullen, Kevin J.; Molitoris, Jason K.; Witek, Matthew; et al. (Otolaryngology-head and neck surgery, 2022)
Objective The study aimed to assess the impact of the coronavirus disease 2019 (COVID-19) pandemic on head and neck oncologic care at a tertiary care facility. Study Design This was a cross-sectional study conducted between March 18, 2020, and May 20, 2020. The primary planned outcome was the rate of treatment modifications during the study period. Secondary outcome measures were tumor conference volume, operative volume, and outpatient patient procedure and clinic volumes. Setting This single-center study was conducted at a tertiary care academic hospital in a large metropolitan area. Methods The study included a consecutive sample of adult subjects who were presented at a head and neck interdepartmental tumor conference during the study period. Patients were compared to historical controls based on review of operative data, outpatient procedures, and clinic volumes. Results In total, 117 patients were presented during the review period in 2020, compared to 69 in 2019. There was an 8.4% treatment modification rate among cases presented at the tumor conference. There was a 61.3% (347 from 898) reduction in outpatient clinic visits and a 63.4% (84 from 230) reduction in procedural volume compared to the prior year. Similarly, the operative volume decreased by 27.0% (224 from 307) compared to the previous year. Conclusion Restrictions related to the COVID-19 pandemic resulted in limited treatment modifications. Transition to virtual tumor board format observed an increase in case presentations. While there were reductions in operative volume, there was a larger proportion of surgical cases for malignancy, reflecting the prioritization of oncologic care during the pandemic.